Dakwah Pengentasan Kemiskinan dalam Pendekatan Teori David ,Mc.Clelland - Anwar, Husen Saeful (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
The concept of poverty reduction, as a religious doctrine (kÃ¢dal fakru an yakÃ»na kufron), that has become a main agenda of daâwah, is not easy to implement so long as the mental attitude of poor people does not allow them to change. In line with this, the main strategy of a daâI has to be that of changing such mental attitude. Mc.Clelland, a development psychologist, provides an operational framework of strategy trough his concept the so-called N-Ach (Need for Achievement). Based on his theory, people would be progressive and prosperous only when they have N-Ach. Man with N-Ach, have strong drive for progress and achievement; be own creativity and innovation, and have strong will to improve his level to better condition. Daâwah can use this theory as a solution to poverty problems.